PENGARUH MODEL KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR GEOGRAFI KELAS X SMA NEGERI 2 PONTIANAK - Mufarrohah, Mufarrohah; Margiati, K.Y; Parijo, Parijo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to know the affect of using cooperative jigsaw model in geography subject toward the students’ achievements at ten grade ii’s students of SMA Negeri 2 Pontianak. The method used in this research was Quasy Experimental Design with nonequivalent control group design and quantitative approach. The data source of this research was primary data wich obtained directly from the students and the data was the post-tests’ score of the ten grade iis students on the material of hydrosphere. The technique of collecting the data used was measurement technique and an instrument in form of questions of objective test. The result showed that the average score of experiment class was 77.56 where the class control was 69.91 with the difference 7.68. the data was analyzed by using t-test. The analysis data showed that the tratio was 3.44 > teritical 1.9967 it meant that the at alternative hypothesis (Ha) which stated that there was a significant difference between the student who taught by using cooperative jigsaw model and the students who taught by using cooperative jigsaw model and the students who taught by using conventional method. The result showed that the affect of using cooperative jigsaw model on the ten grade iis students of SMA Negeri 2 Pontianak was high, that was 0.75. it meant that cooperative jigsaw model has significant affect on the students. Keywords: Influence, Cooperative Model Technique Jigsaw, Learning Outcomes